Recurrent abdominal wall endometriosis at the trocar site of laparoscopy: A rare case - Mojgan Akbarzadeh-Jahromi; Maedeh Motavas; Afsoon Fazelzadeh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Surgical scar endometriosis is typically presented as a slow-growing, painful abdominal mass near the site of a past surgery. Endometriosis on the trocar port site is rare. To best of our knowledge, only 17 cases have been reported in the literature. The nonspecific nature of endometriosis presents a diagnostic challenge, and it is often considered as an incisional hernia or other conditions. Case: Here, we described our experience with a recurrent abdominal scar endometriosis case at the trocar port site of a previous laparoscopy, which was initially thought to be an incisional hernia. Conclusion: Abdominal wall endometriosis should be considered as an important differential diagnosis in females with a positive history of prior abdominal surgery, presented with painful nodule or mass at the site of the surgery.